Clorinda Matto de Turner and Nísia Floresta: Pioneer Female Writers of Indigenism in Latin America - Simon da Silva, Regina (2015)
In this paper I examine the novel Aves sinnido (1889), written by Peruvian authorClorinda Matto de Turner, recognized bythe critics as a precursor of Latin Americanindigenism, as well as the poem Alágrima de um Caeté [A tear of a Caeté](1849) of the Brazilian writer Nísia Floresta.I suggest that the Floresta’s work isa precursor of indigenism in Brazil, evenbefore the work of Matto de Turner. Ialso propose Floresta as one of the firstwriters who developed an approach toLatin American indigenism as a way torecover her work forgotten by the literarycanon in Brazil and, to bring thesecountries closer since they have the indigenoustopic as a literary theme.